TEOLOGI KRISTEN DAN DINAMIKA HUBUNGAN KELUARGA: SUATU KAJIAN LITERATUR PEMBENTUKAN NILAI-NILAI KELUARGA - Weniarti Ta’birampo; Nengsi, Angraini Taburang, Widia Paressa (ADISAM PUBLISHER, 2023)
This study aims to investigate the influence of Christian theology on the dynamics of family relationships and how it shapes the values embraced by family members. This literature review combines detailed analysis of relevant Christian teachings and principles in the context of everyday family life. The significance of parental roles in shaping Christian values is also emphasized in this research. The responsibilities of parents as spiritual leaders and role models are identified as key factors in establishing the foundation of religious values within the family. Additionally, this study examines the role of family prayer and worship in reinforcing Christian values. Contemporary challenges are also explored in this context, with a focus on how modern culture, technology, and environmental factors impact the formation of Christian values within the family. Practical strategies and approaches to address these challenges are also presented. Through the analysis of current literature and relevant case studies, this research provides profound insights into how Christian theology influences the dynamics of family relationships and forms fundamental values for Christian family members. This study offers practical recommendations for Christian families to strengthen and uphold religious values in their daily lives.